Environmental literacy and factors affecting pro-environmental behaviour among year five students in the West Coast of Sabah: a proposed study - Wong, Charmaine Andrea; Mohammad Afandi, Syamsul Herman; Ramachandran, Sridar; Shuib, Ahmad (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
In the last thirty years development in Environmental Education (EE) programs within the Malaysian formal education system has resulted in the current EE across the curriculum program, throughout all primary national schools. However, NGOs and educators have highlighted the need to educate young children on environmental issues, as there still seems to be a gap between what has been advocated and the actual practices in schools. Using a sequential nested mixed methods study, this research aims to assess environmental literacy (EL) among Year 5 national school students in the West Coast of Sabah, using a Primary School Environmental Literacy Instrument. The instrument will cover four EL domains: knowledge; dispositions; competencies; and pro-environmental behaviour (PEB). This study will also explore the factors influencing PEB of these students, and suggest a framework to improve or strengthen environmental literacy. Furthermore, the effects of demographic variables of the Year 5 students on their PEB will also be investigated, while the issues and challenges in implementing EE will be explored through qualitative interviews with key personnel at each school. Other than this, on site observation will be carried out to identify physical evidence that supports PEB at school. The findings of this study will help EE providers and curriculum developers better understand the strengths and weaknesses of the current provisions in developing environmentally literate students. Moreover, it will also provide invaluable information on the factors that influence the development of Year 5 students’ PEB.